ANALYSIS OF MOOD STRUCTURE IN EFL STUDENTS’ NARRATIVE TEXTS - Yovianti Utari (Institut Pendidikan Indonesia Garut, 2023)
This study aimed at finding the types of mood found in students’ narrative texts. This study employed a qualitative research design in which using the document analysis as a technique to obtain the data. The data used in this study were in the form of texts written by the students. There were six students categorized as high achiever, middle achiever and low achiever to become the sample of this study. The data were then analyzed using a data analysis sheet consisting of the categorizations of the data based on the mood types. The findings showed that the dominant mood type of the students’ narrative text was the declarative.